Age‐dependent baseline values of faecal cortisol metabolites in the American mink (Neovison vison) under semi‐natural housing conditions. Issue 3 (3rd September 2013) - Rauch, E.; Bergmann, S.; Hagn, A.; Meixensperger, J.; Reese, S.; Palme, R.; Erhard, M.H.
Summary The welfare of an animal is ensured if it is able to fully satisfy its essential species‐typical needs in all functional aspects of behaviour. In mink, stereotypies and apathy, internal and/or external injuries as well as increased susceptibility to disease have been known to occur as a result of chronic stress. The non‐invasive method of analysing faecal cortisol metabolites (FCM) allows conclusions to be drawn about the stress level in the respective housing system. The objective of this study is to find out how the cortisol metabolites content in the faecal changes with increasing age of the mink under semi‐natural housing conditions. Thus, 40 American mink (Neovison vison) were housed in two outdoor enclosures imitating natural conditions. Throughout the entire study (13th to 32nd week of life), faecal samples were collected to measure cortisol metabolites. No differences in FCM concentrations between the two outdoor enclosures were found. In the young mink lower, less fluctuating FCM levels were found than in older animals. After the first faecal collection in the 13th/14th week of life, the level of metabolites decreased slightly (p = 0.032; 17th/18th week). From the 22nd/23rd week onwards until the 30th/31st week, shortly before the animals were pelted, continuously increasing concentrations were then measured. Increasing FCM levels with advancing age of the animals are probably attributable to the onset of sexual maturity and/or the respective season. This has to be taken into account in future studies using this method for assessing welfare and when comparing different mink housing systems.